3D high resolution clonogenic survival measurement of xrs-5 cells in low-dose region of carbon ion plans. (4th March 2023) - Kartini, Dea; Sokol, Olga; Talabnin, Chutima; Kobdaj, Chinorat; Durante, Marco; Krämer, Michael; Fuss, Martina
Abstract: Purpose: In this study, we performed biological verification measurements of cell survival of a 12 C ion irradiation plan employing a high-resolution 3D culture setup. This allowed, in particular, to access the cell inactivation in the low-dose regions close to the target area. Materials and methods: We established the protocol for a 3D culture setup where xrs-5 cells were grown inside a layered matrigel structure in 384-well plates. Their radiosensitivity to conventional and 12 C ion radiation was evaluated by irradiating them either with 250 kV X-rays at GSI or with monoenergetic 12 C beams of 110 MeV/u at MIT, and compared with those of monolayers. A treatment plan for a rectangular target was prepared using the GSI research treatment planning system TRiP98. xrs-5 cells were seeded in the matrigel-based setup and irradiated in dose fall-off regions using active scanning 12 C ion beams. In addition, film dosimetry utilizing radiochromic EBT3 film has been performed to assess the field homogeneity downstream of 384-well V-bottom plates with or without additional agarose coating of the well plate bottom. Results: Dose response curves following X-ray and 12 C ion irradiation had linear shape and showed a significant decrease in survival fraction at even moderate doses. Survival measurements in the low-dose regions of the plan for the extended target showed good agreement to the predicted survival fraction. The irradiated film profiles yielded a flat dose distribution without apparent artifacts or inhomogeneities for well plates both with and without agarose coating, confirming the suitability of the experimental setup. Conclusions: We conclude that the V-bottom 384-well plates in combination with the radiation-sensitive xrs-5 cell line constitute a suitable radiobiological verification tool which can be used especially for low doses. Furthermore, the measured survival of xrs-5 cells show a good agreement with the expected survival in the low-dose out-of-field regions, both laterally and downstream of the target.